Multi Elements Simulation of Biaxial Test with Two Different Soil Layers Using Hypoplastic Constitutive Model. Issue 1 (June 2021) - Khalaj, O; Abedin Nejad, S; Janda, T
Abstract: Practically, the ground condition usually consists of several layers, which have various properties from each other so it is important to have precise understanding about these layers and their behaviour. For this purpose, two different soil layers in biaxial test was analysed. In the single element simulation, it is impossible to generate the shear strain localization in the porous media but we can get numerous useful results. For strain localization analyse, using multi element models is necessary. The numerical simulation shows that the behaviour of each layer is totally different and the friction angle of both layers changed during simulation.